Regional Incidence of Inflammatory Bowel Disease in a Czech Pediatric Population: 16 Years of Experience (2002-2017) - Jabandziev, Petr; Pinkasova, Tereza; Kunovsky, Lumir; Papez, Jan; Jouza, Martin; Karlinova, Bara; Novackova, Martina; Urik, Milan; Aulicka, Stefania; Slaby, Ondrej; Bohosova, Julia; Bajerova, Katerina; et al. (Journal of pediatric gastroenterology and nutrition, 2020)
OBJECTIVES: Inflammatory bowel disease (IBD) is today a global disease, the incidence of which is growing in the pediatric population. This prospective study aims to decipher IBD incidence and its trend in a pediatric population through 16 years in the South Moravian Region of the Czech Republic. METHODS: We evaluated data concerning 358 pediatric patients with newly diagnosed IBD at University Hospital Brno, which is a gastroenterology center for the entire pediatric population (0-18 years) and cares for all pediatric IBD patients in the South Moravian Region (1,187,667 inhabitants). RESULTS: The study encompassed 3,488,907 children during 16 years. We diagnosed 192 children (53.6%) with Crohn disease (CD), 123 (34.4%) with ulcerative colitis (UC), and 43 (12.0%) with IBD-unclassified (IBD-U). The incidence of IBD increased from 3.8 (CD 2.9, UC 0.9, and IBD-U 0.0) per 100 000/year in 2002 to 14.7 (CD 9.8, UC 4.0, and IBD-U 0.9) per 100,000/year in 2017 (P < 0.001). The overall IBD incidence per 100,000/year was 9.8 (95% confidence interval [CI]: 8.8--10.9). Constituent incidences per 100,000/year were CD 5.2 (95% CI: 4.5--6.0), UC 3.4 (95% CI: 2.8--4.0), and IBD-U 1.2 (95% CI: 0.9--1.6). IBD incidence was projected to reach 18.9 per 100,000/year in 2022. CONCLUSIONS: The overall incidence of pediatric IBD in the Czech Republic is increasing, and especially that of CD, whereas trends in UC and IBD-U appear to be constant. These data highlight the need to identify risk factors involved in the rising incidence of IBD.
Keywords: idiopatické střevní záněty; Czech Republic; dítě; Child; prospektivní studie; Humans; Incidence; Česká republika; Colitis, Ulcerative; Inflammatory Bowel Diseases; incidence; lidé; ulcerózní kolitida; Prospective Studies